Influence of Morphophonological Processes on the Verbal Structure of the Mambwe Language - Pethias Siame; Felix Banda (PT ARRUS Intelektual Indonesia, 2024)
Mambwe language is said to be from the ancestor language, the Fipa in Southern Tanzania. Guthrie (1948) classifies the Mambwe language as M15. This article aims to contribute to describing the verbal structure of Mambwe focusing on the influence of morphophonological processes. Using insights from comparative Bantu morphophonology, descriptive linguistics, elicitation, and direct observation data, the article outlines the prominent morphophonological processes which have an influence on the verbal structure of the language, which include; vowel lengthening, gliding, glide harmony, vowel hiatus, vowel and consonant harmony, vowel deletion, vowel maintenance, assimilation, internal change or zero modification and coalescence. The paper shows that the verbal structure in the prefix, subject, and object marker, and the root is influenced by either the palatal glide [y] or the bilabial glide [w] in the plural, glide maintenance, or glide interchange to harmonise the verbs. It is envisaged such a descriptive analysis will make it easier for curriculum developers to understand the verbal structure of the language and enable them to develop grammar as well as curriculum material.